Modelos de maturidade, um caminho para as organizações alcançarem maturidade em gerenciamento de projetos como diferencial estratégico - Kanup, Wélerson Robaina (2009)
The projects management maturity is bound on the ability of an organization in managing its projects This dissertation has as objective to show to a way them organizations to reach project management maturity as strategical distinguishing. For this we evaluate the theoretical beddings and concepts of the models of management maturity and analyze the application of a model in a non-profit organization of the area of projects management. The bibliographical revision, divides in two parts, introduced the beddings of the projects management and in the second part the beddings of project management maturity. The methodology of research adopted in this dissertation was the application of OPM3 (Organizational Project Management Maturity Model), of PMI (Project Management Institute), in an organization and its analysis. The application of the model was carried through in the directions of the company (vice-presidency, studies technician, administrative, support to the associate, financier and events) and presents in detail the application of the model in the administrative direction. As instrument of collection of data we carry through interviews with the directors of the company and fulfilling of the questionnaire of the tool of the OPM3 Self-Assessment for execution of the evaluation. For analysis of data we also use the tool that after fulfilling of the questions produced a vision in high level or executive - including the list of Better Practical that currently they exist in the organization, and those that do not exist in relation to the Standard Model. The list of Better Practical that they do not exist currently in the organization was referenced as Target Best Practices . The program also generated four graphs, established in the answers: 1) the organization s overall position on a continuum of organizational project management maturity, 2) the organization s maturity in terms of each domain, 3) the organization s maturity in terms of each process improvement stage, and 4) a composed view of graphs 2 and 3. The conclusion showed that projects management maturity is a strategical differential and will be reached with strategical planning directed toward management of projects in the organizations